UNVEILING CULTURAL NARRATIVES THROUGH ANALYZING ASIAN STUDIES PERSPECTIVES OF THE PAKISTAN-INDIA CONFLICT AND KASHMIR'S RIGHT TO SELF-DETERMINATION - Novelliny Arishta Mutya (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This study examines two cultural narratives on the Pakistan- India conflict and the Claim of Kashmir to achieve independence, that is unwarranted since the two nation has been separated in 1947 over the enchanting territory of Jammu and Kashmir. The conflict, centered around territorial disputes, religious disputes, and differences in ideologies, has resulted in widespread human suffering and regional instability, compounded by ethnic and religious heterogeneity, insurgency, and foreign interference. The toll of the Kashmir conflict is not just interstate tensions between the nuclear-armed India and Pakistan but also intrastate violence and widespread human rights abuses. These works bring to light the need for recognition of past wrongs, acceptance of religious diversity and comprehensive restoration and reconciliation process which constitutes the necessity of continuing the dialogue and seeking support on the international level for achieving the lasting and mutually acceptable solution and nonviolence protection of the rights and dignity of the people of Kashmir.